Plant-mediated synthesis of gold nanoparticles from Virola oleifera resin: optimization, characterization and cytotoxicity evaluation - Rafaella de Resende Marques; Marcelo Raul Romero Tappin; Licinio Fontoura; Virginia Garcia Correia; Marcio Soares; Daniel Adesse; Ana Maria Percebom Sette da Silva; Franccesca Fornasier; Mariana Gisbert Jardim dos Santos; Tommaso Del Rosso; Rachel Ann Hauser-Davis; Enrico Mendes Saggioro (Nanotechnology for Environmental Engineering, 2026)
Plant-mediated green synthesis has emerged as a sustainable and cost-effective strategy for the production of gold nanoparticles (AuNPs). In this study, gold nanoparticles were synthesized using an aqueous extract of Virola oleifera resin (AuNPs-Vo), and their synthesis parameters were optimized through factorial experimental design, followed by physicochemical characterization and cytotoxicity assessment. Factorial experimental designs were applied to identify optimal conditions for obtaining stable, concentrated, and monodisperse nanoparticles, evaluating extract concentration, pH, temperature, reaction time, and agitation. The plant extract was characterized by High-Performance Liquid Chromatography coupled with Ultraviolet–Visible Detection (HPLC-UV/Vis) and Liquid Chromatography–Mass Spectrometry (LC-MS), while the nanoparticles were analyzed by UV-Vis (Ultraviolet–Visible Spectroscopy), Transmission Electron Microscopy (TEM), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), Dynamic Light Scattering (DLS), zeta potential, and Raman spectroscopy. Nanoparticle stability was evaluated through flocculation assays under different pH, temperature, and ionic strength values. Cytotoxicity was assessed in Vero cells employing 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays after exposure to three AuNPs-Vo concentrations and their precursors (extract and HAuCl 4 ), along with the analysis of oxidative stress biomarkers: Reduced Glutathione (GSH), Glutathione S-transferase (GST), Hydrogen Peroxide (H₂O₂), Catalase (CAT), Malondialdehyde (MDA), Protein Carbonyl (PTC or Carb) and Total Antioxidant Capacity (CAOT). The most influential synthesis parameters were pH, reaction time, and extract concentration, with optimal conditions (about concentration and size) at pH 8.3, 6 minutes, and 1.0 mg mL⁻ 1 , respectively. Polyphenols, polyols, and flavones were identified as key agents for the reduction and stabilization of Au 3 ⁺. The AuNPs-Vo presented an average gold concentration of 21 mg L⁻ 1 , predominantly spherical morphology, particle sizes of 15–21 nm, negative surface charge, and high stability at pH 3–9. Cytotoxicity assays demonstrated high cell viability (> 85%) and no significant induction of oxidative stress (p > 0.05), indicating low toxicity compared to precursor reagents. In some exposures to AuNPs-Vo, there was a significant decrease in carbonylated proteins (approximately 50%). These findings highlight the potential of phytochemicals derived from Virola oleifera as sustainable reducing agents for the production of stable compounds with promising applications.

Metallothionein-2 and Heat Shock Protein 70 liver and brain gene expressions and correlations with metal(loid) contamination in a critically endangered free-ranging elasmobranch, the Brazilian Guitarfish (Pseudobatos horkelii) - Maria Carolina Peixoto-Rodrigues; Heloise Martins de Souza; Lucas José Guimarães; Júlia Vianna de Pinho; Tatiana Dillenburg Saint’Pierre; Daniel Adesse; Rachel Ann Hauser-Davis (Journal of Hazardous Materials, 2026)

Early-life exposure to PCBs and PFAS exerts negative effects on the developing central nervous system - Maria Carolina Peixoto-Rodrigues; José Raphael Monteiro-Neto; Timea Teglas; Michal Toborek; Natalia Soares Quinete; Rachel Ann Hauser-Davis; Daniel Adesse (Journal of Hazardous Materials, 2025)

Shark-on-a-dish: Elasmobranch cell cultures as a promising tool for the conservation of threatened species - Maria Carolina Peixoto-Rodrigues; Daniel Adesse; Marcelo Vianna; Rachel Ann Hauser-Davis (Marine Pollution Bulletin, 2025)

Microglial NLRP3 Inflammasome Induces Excitatory Synaptic Loss Through IL-1β-Enriched Microvesicle Release: Implications for Sepsis-Associated Encephalopathy - Carolina A. Moraes; Eugenio D. Hottz; Débora Dos Santos Ornellas; Daniel Adesse; Carolina T. de Azevedo; Joana C. d’Avila; Camila Zaverucha-do-Valle; Tatiana Maron-Gutierrez; Helene Santos Barbosa; Patricia Torres Bozza; Fernando Augusto Bozza (Molecular Neurobiology, 2023)